Evaluation of material waste, dimensional stability, and detail reproduction of polyvinyl siloxane impression materials mixed with different mixing tips - Maluly-Proni, Ana Teresa [UNESP]; Delben, Juliana Aparecida; Briso, André Luiz Fraga [UNESP]; Marson, Fabiano Carlos; dos Santos, Paulo Henrique [UNESP] (Elsevier, 2021)
Statement of problem: Redesigned mixing tips, promising less impression material waste, have been marketed. However, whether their use adversely affects the dimensional stability and detail reproduction of the impression material is unclear. Purpose: The purpose of this in vitro study was to evaluate the dimensional stability, detail reproduction, and material waste of different polyvinyl siloxane impression materials (regular and light-body) mixed with 2 different mixing tips (MIXPAC T-Mixer mixing tip and MIXPAC helical mixing tip). Material and methods: Six different polyvinyl siloxane impression materials were used in 2 different consistencies: Virtual Monophase and Virtual Light Body (Ivoclar Vivadent AG), Express XT Regular and Express XT Light Body (3M ESPE), and Panasil initial contact Regular and Panasil initial contact Light (Kettenbach). The polyvinyl siloxane impression materials were mixed with 2 different mixing tips: conventional helical and T-Mixer (n=10). The specimens were prepared in a metal matrix as per specification #19 of the American National Standards Institute/American Dental Association (ANSI/ADA) and International Organization for Standardization (ISO) 4823:2015. The materials were mixed with both mixing tips as per the manufacturer's instructions, inserted into a perforated custom tray on the matrix, and allowed to polymerize completely. The dimensional stability was calculated based on the measurement of the reproduction of lines engraved in the metal matrix. Detail reproduction was evaluated through analysis of continuity and reproducibility of those lines, immediately, 7 days, and 14 days after polymerization. Material waste was assessed by the difference between the initial (before mixing) and final weight (after complete polymerization) of both mixing tips. The data on dimensional stability and detail reproduction among the materials were submitted to the Kruskal-Wallis test, followed by the Student-Newman-Keuls test (α=.05). Comparison between the mixing tips was carried out with the Mann-Whitney test (α=.05), while the comparison among the periods of analysis (immediate, 7 days, and 14 days) was carried out with the Friedman test (α=.05). The data on material waste between the mixing tips were submitted to 1-way ANOVA, followed by the Tukey honestly significant difference tests (α=.05). Results: The T-Mixer mixing tip resulted in reduced material waste. For dimensional stability, Virtual Light mixed with T-Mixer resulted in lower dimensional change (0.53 ±0.58%) compared with the helical mixing tip (1.09 ±0.43%). Among the materials, Panasil Light presented higher values of dimensional change at immediate and 7-day analysis when mixed with T-Mixer tip with a statistical difference compared with Express Light, Virtual Light, and Panasil Regular (P<.05). In general, both mixing tips provided similar results in all periods of analysis (P>.05) for qualitative analysis of detail reproduction. Conclusions: The T-Mixer tip resulted in less material waste compared with the helical mixing tip. In general, light-body materials showed higher dimensional stability when the T-Mixer tip was used compared with the conventional tip. In general, reduced detail reproduction was observed after periods longer than 7 days after impression making.